2019
DOI: 10.1080/23789689.2019.1681819
|View full text |Cite
|
Sign up to set email alerts
|

Using rainfall measures to evaluate hydrologic performance of green infrastructure systems under climate change

Abstract: Samaras (2019): Using rainfall measures to evaluate hydrologic performance of green infrastructure systems under climate change, Sustainable and Resilient Infrastructure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…Unfortunately, no matter what size of infrastructure is selected, it is likely to experience increased variability and increases in short-duration, high-intensity rain storms. Tracking performance over time for both green and gray infrastructure, and using adaptable design principles will ensure communities are prepared for many future states (Cook et al 2019). For instance, if a larger pipe size is selected, municipalities should plan to flush pipes during periods of drought, whereas smaller pipe sizes will likely need distributed green infrastructure placed upstream in order to send flows into pipes more slowly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, no matter what size of infrastructure is selected, it is likely to experience increased variability and increases in short-duration, high-intensity rain storms. Tracking performance over time for both green and gray infrastructure, and using adaptable design principles will ensure communities are prepared for many future states (Cook et al 2019). For instance, if a larger pipe size is selected, municipalities should plan to flush pipes during periods of drought, whereas smaller pipe sizes will likely need distributed green infrastructure placed upstream in order to send flows into pipes more slowly.…”
Section: Discussionmentioning
confidence: 99%
“…To create climate-corrected IDF curves, many apply MOS techniques to the continuous rainfall time series as the first step in the process, through bias correction (Cannon et al 2015;Kuo et al 2015;Kueh and Kuok 2016), weather typing (Mandal et al 2016b), or weather generators (Wilks and Wilby 1999). The extreme rainfall events extracted from these continuous series (i.e., the annual maximum or partial duration series) can also be adjusted, e.g., through quantile mapping (Srivastav et al 2014b), genetic programming (Hassanzadeh et al 2013), or historical analogs (Castellano and DeGaetano 2016). Finally, the intensity of rainfall (return level), evaluated after the GEV is fit to the extreme events, can also be adjusted, usually using a change factor that is a ratio calculated from historical and future climate model return levels (Forsee and Ahmad 2011;Zhu et al 2012;Cook et al 2017).…”
Section: Choice Of Spatial Adjustment (Mos) Techniquementioning
confidence: 99%
“…Expert elicitation can sometimes be perceived as a low‐effort alternative to computationally intensive analysis, but it is also time consuming, requires careful consideration of the questions being asked, and is, by definition, subjective and influenced by human bias (Morgan, 2014). Finally, using rainfall measures as a proxy to track or predict the hydrologic performance of green infrastructure, may provide a less data and computationally intensive method under uncertainty than hydrologic simulation and on‐site sensors (Cook et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is also evident from Figure 4, the dotted lines of the 100-and 50-year are closer to the upper bound (2070-2099 timeframe) compared to the 2-and 10-year return periods. Previous studies have also shown that GI has lower performances for larger rainfall events (Cook et al, 2019;Vaillancourt et al, 2019), since the GI soil and media may reach saturation, hence providing less storage capacity. Webber et al (2020) also found the trend of diminishing effectiveness of GI in reducing flood peak as events become more intense, i.e., associated with a lower probability of occurrence.…”
Section: Gi Mitigation Impact-cso Total Volume Comparison Between W/ and W/o Ppmentioning
confidence: 99%